Factors Influencing the Deaggregation of Human and Rabbit Platelets - Kinlough-Rathbone, R L; Mustard, J F; Perry, D W; Dejana, E; Cazenave, J-P; Packham, M A; Harfenist, E J (Thrombosis and Haemostasis, 1983)
The mechanisms involved in platelet deaggregation are unclear. Washed platelets from rabbits or humans aggregated by ADP can be deaggregated by EDTA or PGI2 if the release reaction has not occurred; during deaggregation 125I-fibrinogen dissociates from the platelets. Human platelets suspended in a medium without calcium undergo the release reaction during ADP-induced aggregation; EDTA, PGE, or PGI2 do not deaggregate these platelets although EDTA displaces much of the 125I-fibrinogen that associates with them during aggregation. Rabbit platelets aggregated by low concentrations of releaseinducing stimuli (sodium arachidonate, collagen or thrombin) can be deaggregated by EDTA, PGI2 or PGE1 and 125I-fibrinogen dissociates from them; with high concentrations of collagen or thrombin, deaggregation and dissociation of l25I-fibrinogen is slower. Human platelets that have undergone the release reaction in response to thrombin, collagen or a combination of sodium arachidonate and ADP are not readily deaggregated by EDTA or PGE1. Since aggregation and fibrinogen binding involving the glycoprotein IIb/IIIa complex are readily reversed by EDTA, and since Ca2+ is required for thrombospondin binding to activated platelets, there may be a third type of platelet-platelet adherence that is not disrupted by EDTA; this type of binding plays a greater role with human than with rabbit platelets.
Keywords: Platelets; Deaggregation; Fibrinogen; Release reaction; Prostaglandin E1; Thrombin; ADP